Study on energy dissipation law of vibration disturbance damaged Zhanjiang Formation structural clay - Yanhua Xie; Bin Tang; Shuaiyu Liu; Binghui Zhang (PLoS ONE, 2025)
This study aims to investigate the energy dissipation laws and underlying mechanisms of damage in Zhanjiang Formation structural clay following vibrational disturbances. Based on the test results of the unconfined compressive strength of the disturbed Zhanjiang Formation structural clay, and in conjunction with theories related to energy dissipation, the analysis revealed that: (1) An increase in the disturbance degree leads to higher compaction strain and compaction dissipation energy, thereby enhancing the ductility of the sample; (2) Although disturbance reduces the strength of the sample, it increases its deformation capacity, indicating that the interplay between strength and deformation affects the level of energy dissipation; (3) The variation in the logarithmic value of the elastic energy dissipation ratio can be categorized into three phases: initial lgK > 0; lgK < 0 to (lgK)min; and an increase from (lgK)min, with (lgK)min marking the critical turning point for the transition from the elastic to the plastic phase of the soil. The study also profoundly analyzed the dynamic regulation mechanisms of vibrational disturbance energy from two perspectives: dynamic regulation and structural change, as well as energy dissipation and damage evolution. High-frequency vibrations expedite the damage process, and post-damage energy dissipation involves friction, microcrack propagation, and plastic deformation, ultimately leading to the collapse of the soil structure. This study not only enhances the understanding of the complex mechanical behavior of such soils but also paves the way for innovative applications and theoretical advances in soil mechanics.